Chapter Carlo Cipolla, Amedeo Crivellucci e l'edizione della Historia Langobardorum di Paolo Diacono - ZABBIA, Marino (Reti Medievali E-Book, 2021)
During the congress on Paolo Diacono held in Cividale del Friuli in 1899 (eleven centuries after Paolo's death) a scientific committee decided to publish a new edition of Paolo's opera omnia. A sort of scholar jealousy arised: the Istituto storico italiano thought that its own duty was to publish the Historia romana and the Historia Langobardorum, the main works written by Paolo. The eminent scholar Carlo Cipolla, on the contrary, believed that task was of the Deputazione veneta di storia patria. A compromise was signed: Amedeo Crivellucci (of the Istituto storico) invited Cipolla to collaborate on the edition of both Histories. The present essay recalls that collaboration (that unfortunately was interrupted in 1904) studying the correspondence between Cipolla, Crivellucci and other historians (Villari, Crivellucci) and reopening an unknown page of the history of Italian medievistic scholarship.